Numerical study of concrete spall damage to blast loads - Li, Jun; Hao, Hong (Pergamon, 2014)
Spall damage is a typical damage mode of concrete structures under blast or high velocity impact loads. Blast and impact loads generate a stress wave propagating in the structure. At the opposite side from which the structural element is impulsively loaded, spall will occur if the net primary stresses over an area exceed the concrete dynamic tensile strength and the resistance force such as the material dynamic bond and interlock. Fragments of structural element generated from spall damage could eject with largevelocities, and impose significant threats to equipment and personnel even it does not necessarily greatly reduce the load carrying capacity of the structural components. In the present study, spall damage of generic reinforced concrete columns subjected to blast loads is investigated numerically. Three-dimensional numerical models are developed to predict the concrete spalling under blast loads. The accuracy of the numerical simulations is verified with blast testing data reported by other researchers. Intensivenumerical simulations are then carried out to investigate the influences of the column dimensions and reinforcement mesh on concrete spall damage. Based on numerical simulation data, empirical relations are suggested to predict concrete spall damage based on explosion scenarios, column dimensions andreinforcement conditions.